2019
DOI: 10.1155/2019/8260583
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen-to-Albumin Ratio Predicts Contrast-Induced Nephropathy in Patients after Emergency Percutaneous Coronary Intervention

Abstract: Background The aim of the present study was to investigate the association between fibrinogen-to-albumin ratio (FAR) with contrast-induced nephropathy (CIN) in patients undergoing emergency percutaneous coronary intervention (PCI). Methods 565 patients with emergency PCI were consecutively enrolled. The primary outcome was CIN defined as either a 25% increase in baseline serum creatinine levels or a 0.5 mg/dL (44 μmol/L) increase in absolute serum creatinine levels within 72 h after the contrast medium exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…7,8,27 Inflammatory markers and some risk scores, including WBC count, NLR, PLR, CRP, albumin, CRP-to-albumin ratio, fibrinogen and procalcitonin, thrombolysis in myocardial infarction, and Predicting Bleeding Complications in Patients Undergoing Stent Implantation and Subsequent Dual Antiplatelet Therapy score have been identified to be related with CIN risk in ACS cases. 915,2833 Similar to previous studies, there was no significant difference between the WBC and platelet counts between the groups that developed and did not develop CIN, while neutrophil counts were higher and lymphocyte counts were lower in the CIN group, and CRP, NLR, and PLR were also higher in the CIN group in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…7,8,27 Inflammatory markers and some risk scores, including WBC count, NLR, PLR, CRP, albumin, CRP-to-albumin ratio, fibrinogen and procalcitonin, thrombolysis in myocardial infarction, and Predicting Bleeding Complications in Patients Undergoing Stent Implantation and Subsequent Dual Antiplatelet Therapy score have been identified to be related with CIN risk in ACS cases. 915,2833 Similar to previous studies, there was no significant difference between the WBC and platelet counts between the groups that developed and did not develop CIN, while neutrophil counts were higher and lymphocyte counts were lower in the CIN group, and CRP, NLR, and PLR were also higher in the CIN group in our study.…”
Section: Discussionsupporting
confidence: 88%
“…68 Several inflammatory markers, such as C-reactive protein (CRP), CRP-to-albumin ratio, and fibrinogen-to-albumin ratio have been proposed to be associated with CIN in various clinical conditions including acute coronary syndrome (ACS). 912 In addition, some hematological parameters such as neutrophil, lymphocyte, platelet counts, and other derived parameters such as neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been reported to predict CIN. 1315 Recently, a novel inflammatory marker defined as systemic immune-inflammation index (SII) has been proposed to be more valuable than either NLR or PLR alone in predicting inflammatory status and prognosis in various clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…27 FAR, a novel inflammatory index, reflects both overactive coagulation and inflammatory pathways, both of which are potential mechanisms for CI-AKI. 28,29 This hypothesis is supported by the correlation between FAR and CRP in previous studies. 30 Although the exact mechanism of high inflammatory state and the occurrence of CI-AKI is not known.…”
supporting
confidence: 68%
“…Of note, studies have recently found that elevated FAR level is associated with the occurrence of PC-AKI. You et al [ 18 ] found that elevated FAR can predict PC-AKI in acute myocardial infarction with an AUC of 0.721 (95% CI: 0.68–0.76). Ertas et al [ 17 ] reported that FAR is an independent predictor of PC-AKI in patients undergoing carotid angiography, and they found that FAR can significantly improve risk reclassification for PC-AKI over fibrinogen and albumin alone.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen-to-albumin ratio (FAR), a novel inflammation-based risk index, has been found to be valuable in predicting the poor outcomes in cancers [ 12 , 13 ] and cardiovascular diseases [ 14 16 ]. Recently, studies have shown that preprocedural FAR levels are associated with PC-AKI occurrence in patients after carotid angiography [ 17 ] and emergency PCI [ 18 ]. However, to date, no study has investigated the potential association between the FAR and the risk for PC-AKI in non-acute patients undergoing elective PCI.…”
Section: Introductionmentioning
confidence: 99%